Corinthian column-krater - Astarita Painter
"The mission of Menelaus and Ulysses to Troy to regain Helen is represented. The two heroes with the herald Talthybios are seated on the steps of Athena's sanctuary and are being welcomed by the priestess Theano, wife of Antenor. She is accompanied by three maidservants and a procession of riders, perhaps her sons."